أثر الإدارة الألكترونية في تحسين أداء المؤسسات بالجزائر - موسى, إكرام (My University, 2024)
This study aimed at the effects of e-governance on improving institutional performance and, Naktal Foundation in Mustaganam State has been selected as a modus operandi, Through this we stood on the most important pillars of e-governance and examined its effectiveness by evaluating the organization's performance. We finally found that real electronic transformation is about the enterprise's ability to successfully use technological technologies and take advantage of new procedures that enable us to operate faster and less expensive and wrong. Regardless of location and time, where to apply it requires a combination of manpower of appropriate human, technical and institutional elements, E-management has also contributed to enhancing staff performance and improving decision-making effectiveness, improving organizational performance in all aspects of the organization.
دراسة حالة مؤسسة نفطال مستغانم
Keywords: الإدارة الإلكترونية ،تكنولوجيا المعلومات والإتصال ،الأداء المؤسسي ،